Anscombe’s Account of Voluntary Action in “Intention” - Jean-Philippe Narboux (Enrahonar: Quaderns de Filosofia, 2020)
It might seem that Anscombe’s book Intention dismisses the concept of the voluntary as of secondary philosophical significance. However, this impression is misconceived and stems from a misunderstanding of Anscombe’s philosophy of action in general and the contribution of Intention in particular. The main contention of this essay is that to understand the scope and nature of the contribution of Intention to an understanding of the voluntary we must come to terms with not only the positive account that the book advances on the basis of its methods but also the nature of the problems that it deliberately leaves out, based on these same methods, on the grounds that they involve considerations pertaining to ethics. This essay is divided into seven sections. The introductory section expounds the charge that Intention relegates the concept of the voluntary into the periphery of the philosophy of action. The next section places §49 within Intention as a whole. It seeks to explain why a systematic account of the voluntary is deferred until such a late stage in the inquiry. I then proceed to give a commentary of section §49 with the aim of unpacking and defending the various insights that are there systematically brought together against the background of the pivotal distinction between the intentional and the voluntary. Sections 3 to 6, which constitute the main bulk of this essay, are respectively devoted to the four headings under which Anscombe successively apprehends the distinction between the intentional and the voluntary in §49. Finally, in the last section, I try to bring out the underlying unity of the account of the voluntary given in §49 as well as the deliberate nature of the limitations in this account.